"Everyone knows me …. I sort of like move about": The friendships and encounters of young people with Special Educational Needs in different school settings. (June 2017) - Holt, Louise; Bowlby, Sophie; Lea, Jennifer
This paper examines the peer-related social experiences and friendships of young people (aged 11–17) diagnosed with Special Educational Needs in four different school settings: two mainstream schools with special units and two special schools in Southeast England, UK. Findings from qualitative research involving young people with Special Educational Needs and adults, and participant observation, are presented. The young people had one or a combination of the following diagnoses of Special Educational Need: 'Moderate Learning Difficulties', on the 'Autistic Spectrum', and 'Social, Emotional and Mental Health Difficulties'. We use the term 'differences' rather than 'difficulties' to express the interconnected socio-spatial construction of, and corporeality of, the experiences of these differences. There has been limited scholarship about the social experiences of young people with these diagnoses. In our study, young people's experiences of friendships, exclusion, inclusion and bullying were socio-spatially shifting. Young people had varying experiences in the different school settings. In all settings, most had friends within the school, although those in special schools and units tended to have more friends within the school. However, bullying and 'othering' were also experienced in all three settings based on a variety of perceived 'differences'. All young people needed opportunities for 'encounter' to forge friendships. Encounters are risky and can reproduce and reinforce difference as well as generating social connections and friendships. In many spaces, young people's opportunities for encounter were constrained by the socio-spatial organisation of schools.